2013
DOI: 10.1002/smll.201302856
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Helical Magnetic Microrobots Obtained by 3D Template‐Assisted Electrodeposition

Abstract: Hybrid helical magnetic microrobots are achieved by sequential electrodeposition of a CoNi alloy and PPy inside a photoresist template patterned by 3D laser lithography. A controlled actuation of the microrobots by a rotating magnetic field is demonstrated in a fluidic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
118
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 15 publications
(21 reference statements)
0
118
0
Order By: Relevance
“…In the multi-robot perspective, each individual robot could be either identical (i.e., homogeneous) with the same functions or different (i.e., heterogeneous) with varying functionality [48]. The team could move deterministically or stochastically using on-board or off-board (remote) actuation methods [48], [136], [138]–[140]. As locomotion, they could swim, crawl, roll, spin, or hop [30], [33], [50], [61], [136], [138], [141].…”
Section: Challenges and Emerging Concepts In Miniaturized Biomedmentioning
confidence: 99%
“…In the multi-robot perspective, each individual robot could be either identical (i.e., homogeneous) with the same functions or different (i.e., heterogeneous) with varying functionality [48]. The team could move deterministically or stochastically using on-board or off-board (remote) actuation methods [48], [136], [138]–[140]. As locomotion, they could swim, crawl, roll, spin, or hop [30], [33], [50], [61], [136], [138], [141].…”
Section: Challenges and Emerging Concepts In Miniaturized Biomedmentioning
confidence: 99%
“…Electro-optical polymer based devices are another area of study which has been taking advantage of the MPM as a powerful characterization method [9]. Moreover, recent studies showed the ability of utilizing MPM in three dimensional micro-fabricated devices including sensors, waveguides, photonic structures, and biomedical devices, using various types of light sensitive polymers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this field, some research has been directed to the fabrication method of the microbot prototypes [15,16], to their control and propulsion [17][18][19][20][21][22], and to the study of their communication mechanisms [23][24][25]. It is well known that at a low-Reynolds number regime, non-reciprocal motion is required for a self-propelling device.…”
Section: Introductionmentioning
confidence: 99%